Reaction Mechanism of Oxygenate Components of Biomass Pyrolysis Oil on HZSM-5 Zeolite - Yang, Haiqing; Xu, Qingli; Li, Hongyu; Wang, Fu; Yan, Yongjie (Asian Journal of Chemistry, 2012)
In this paper, phenol, m-cresol and cyclopentanone, chosen as model compounds, were catalyzed upgrading at 500 ºC, space velocity 5.0 h-1 and different water content conditions. The results showed that the phenol can't be catalyzed on the phase of zeolite HZSM-5. According to the catalytic pyrolysis products of m-cresol and cyclopentanone, simply catalytic reaction pathways were speculated that m-cresol cracking included demethylation and isomerizate reactions and cyclopentanone cracking was firstly dehydration or decarbonylation and then cyclized to produce cyclocompounds, which provided a theoretical basis for the bio-oil catalytic pyrolysis mechanism research.